Exploring the Staycation Phenomenon After COVID-19: A Grounded Theory Approach - Desy Maya Indriana; Indah Nur Syamsi Aguston; Maysheilla Chandra; Jerry Heikal (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The staycation phenomenon has received significant attention in recent years, especially during the pandemic, as more and more people choose to spend their free time close to home. However, the staycation phenomenon does not necessarily disappear when the pandemic ends, as many people, especially urban dwellers, still choose to do staycations as an alternative vacation. The continuous interest in staycations underscores the need for a deeper exploration of the motivations, experiences, and implications associated with this recreational trend. Therefore, this research employs a grounded theory approach to delve into aspects of the staycation phenomenon, aiming to provide a comprehensive understanding of its dynamics and impacts. Researchers conducted direct interviews with several millennial participants (aged 27 – 37 years old), seeking to uncover the fundamental factors driving individuals’ decisions to choose staycations. By elucidating the determinants of staycation choice, this study is expected to contribute to the fields of recreation studies, and tourism, and provide fresh insights that can be utilized by the hospitality industry or related associations to enhance their services, thus ensuring that staycations remain a sustainable and inclusive recreational option for diverse populations. Based on the research results, the researchers obtained coding results of 42 from 9 respondents which were then classified into 19 categories and 13 themes: Location, Reviews, Price, Facility, Services, Proximity to the culinary / souvenir area, Healing, Cozy Place, Quality, Activity in Hotel, Me-time, Looking for New Atmosphere, Bonding. The highest scores that drive individual decisions in choosing a staycation is Healing.